Health‐related quality of life in older adult survivors of selected cancers: Data from the SEER‐MHOS linkage. Issue 5 (4th November 2014) - Kent, Erin E.; Ambs, Anita; Mitchell, Sandra A.; Clauser, Steven B.; Smith, Ashley Wilder; Hays, Ron D.
<x xml:space="preserve">Abstract</x> BACKGROUND Research on health‐related quality of life (HRQOL) among older adult cancer survivors is mostly confined to breast cancer, prostate cancer, colorectal cancer, and lung cancer, which account for 63% of all prevalent cancers. Much less is known about HRQOL in the context of less common cancer sites. METHODS HRQOL was examined with the 36‐Item Short Form Health Survey, version 1, and the Veterans RAND 12‐Item Health Survey in patients with selected cancers (kidney cancer, bladder cancer, pancreatic cancer, upper gastrointestinal cancer, cancer of the oral cavity and pharynx, uterine cancer, cervical cancer, thyroid cancer, melanoma, chronic leukemia, non‐Hodgkin lymphoma, and multiple myeloma) and in individuals without cancer on the basis of data linked from the Surveillance, Epidemiology, and End Results cancer registry system and the Medicare Health Outcomes Survey. Scale scores, Physical Component Summary (PCS) and Mental Component Summary (MCS) scores, and a utility metric (Short Form 6D/Veterans RAND 6D), adjusted for sociodemographic characteristics and other chronic conditions, were calculated. A 3‐point difference in the scale scores and a 2‐point difference in the PCS and MCS scores were considered to be minimally important differences. RESULTS Data from 16, 095 cancer survivors and 1, 224, 549 individuals without a history of cancer were included. The results indicated noteworthy deficits in physical health status. Mental health was comparable, although scores for the Role–Emotional and Social Functioning scales were worse for patients with most types of cancer versus those without cancer. Survivors of multiple myeloma and pancreatic malignancies reported the lowest scores, with their PCS/MCS scores less than those of individuals without cancer by 3 or more points. CONCLUSIONS HRQOL surveillance efforts revealed poor health outcomes among many older adults and specifically among survivors of multiple myeloma and pancreatic cancer. Cancer 2015;121:758–765. © 2014 American Cancer Society.